Comparison of health-related quality of life of cancer patients undergoing first and last follow-up after robotic surgery: A meta-analysis - Fidan, Cuma (Elsevier Sci Ltd, 2026)
Background: The primary objective of this study is to compare health-related quality of life (HRQoL) of cancer patients undergoing first and last follow-up after robotic surgery (RS). The secondary objective of the study is to reveal effect of moderator variables on HRQoL of cancer patients after surgery. Methods: Random effects model was used for meta-analysis, sensitivity, publication bias, meta-anova and metaregression analyses. Threshold values have been calculated to evaluate clinical significance. Results: 13 studies were included in the meta-analysis (total of 2.399 cancer patients). Results of meta-analysis and sensitivity analysis show that cancer patients undergoing last follow-up after RS have better HRQoL than first follow-up. There is no publication bias. Results of meta-anova analysis show that (1) RS method has better HRQoL than other methods, (2) In gynaecologic cancers, cancer patients undergoing last follow-up after RS have better HRQoL than first follow-up, and (3) In cases where difference between last and first follow-up after RS is above or below 43, cancer patients undergoing last follow-up have better HRQoL than first follow-up. These results are both statistically and clinically significant. Conclusion: RS treatment is effective in terms of HRQoL in cancer patients, both statistically and clinically. Therefore, RS treatment improves HRQoL of cancer patients. The results of this study could help surgeons develop patient-centred treatment strategies.
Keywords: Cancer Patients; Clinical Significance; Health-Related Quality Of Life; Meta-Analysis; Robotic Surgery